Frequency and Risk Factors for Hyperglycemia in Children with Acute Lymphoblastic Leukemia During Induction Chemotherapy - Ahammed, Md Tanvir (Bangladesh Journal of Child Health, 2022)
Background: Hyperglycemia is a common side effect and it has long been recognized as a consequence of corticosteroids and L-asparaginase, chemotherapeutic agents key to ALL treatment. This study was done to determine the frequency and identify the risk factors for hyperglycemia in paediatric ALL during induction chemotherapy. Material & Methods: This prospective observational study was done among 87 newly diagnosed ALL cases of 1-18 years of age. After initial work up patient got induction chemotherapy according to UK ALL 2003 (modified) protocol in BSMMU. Anthropometric measurements and CBC, RBS/ 2 hours after glucose/ FBS and corresponding urine sugar was assessed after 2nd, 4th, 6th and 9th dose of Lasparaginase and after completion of induction. Data were analyzed by SPSS 17.0. Results: Eight patients (9.75%) of the study cohort developed hyperglycemia. Among ³10 years of age 36.8% had hyperglycemia compared to 1.6% of younger children (p<0.001). No gender difference was found. Obese and overweight (p <0.001 in both cases), positive family history of diabetes mellitus using 4 drugs during induction remission phase of chemotherapy were found significant risk factors for hyperglycemia. Conclusion: In this study frequency of hyperglycemia was 9.75% and frequency of transient hyperglycemia (TH) was 7.3%. Older age, obese or overweight children, positive family history of diabetes mellitus, patient getting regimen B according to UK-ALL 2003 (modified) protocol had shown increase the risk of hyperglycemia. BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 155-161